Global Profiling of Metabolic Adaptation to Hypoxic Stress in Human Glioblastoma Cells - Kucharzewska, Paulina; Christianson, Helena C.; Belting, Mattias (PLOS ONE, 2015)
Oncogenetic events and unique phenomena of the tumor microenvironment together induce adaptive metabolic responses that may offer new diagnostic tools and therapeutic targets of cancer. Hypoxia, or low oxygen tension, represents a well-established and universal feature of the tumor microenvironment and has been linked to increased tumor aggressiveness as well as resistance to conventional oncological treatments. Previous studies have provided important insights into hypoxia induced changes of the transcriptome and proteome; however, how this translates into changes at the metabolite level remains to be defined. Here, we have investigated dynamic, time-dependent effects of hypoxia on the cancer cell metabolome across all families of macromolecules, i.e., carbohydrate, protein, lipid and nucleic acid, in human glioblastoma cells. Using GC/MS and LC/MS/MS, 345 and 126 metabolites were identified and quantified in cells and corresponding media, respectively, at short (6 h), intermediate (24 h), and prolonged (48 h) incubation at normoxic or hypoxic (1% O2) conditions. In conjunction, we performed gene array studies with hypoxic and normoxic cells following short and prolonged incubation. We found that levels of several key metabolites varied with the duration of hypoxic stress. In some cases, metabolic changes corresponded with hypoxic regulation of key pathways at the transcriptional level. Our results provide new insights into the metabolic response of glioblastoma cells to hypoxia, which should stimulate further work aimed at targeting cancer cell adaptive mechanisms to microenvironmental stress.